PENGARUH KESEMPATAN KERJA DAN UPAH MINIMUM TERHADAP PENGANGGURAN DAN TINGKAT KEMISKINAN KABUPATEN/KOTA DI PROVINSI BALI - Nanda Erayanti, Putu Ayu Wulan; Suasih, Ni Nyoman Reni (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 12 No 12 (2023): Vol.12.No.12. DESEMBER 2023DO - 10.24843/10.24843/EEP.2023.v12.i12.p01, 2023)
One of the recurring economic issues is the challenge of poverty faced by various countries worldwide, including Indonesia. Poverty is evident through a high number of unemployed individuals. Those living in poverty and those facing unemployment generally encounter difficulties in accessing job opportunities, limited business development, income disparities, and lack of workplace protections, especially for women. These issues also affect economically disadvantaged groups in society. This study aims to analyze the impact of job opportunities and minimum wage on unemployment and poverty rates in the Regencies/Cities of Bali Province. The research utilizes secondary data from the period 2012-2021. The study covers 9 Regencies/Cities within Bali Province. Path Analysis is the employed analytical technique. The findings of this research indicate that: 1) Job opportunities have a significant negative impact on unemployment, while minimum wage has a significant positive impact on unemployment. 2) Job opportunities have a positive but insignificant impact on the poverty rate, while minimum wage has a significant negative impact on the poverty rate. Unemployment, on the other hand, has a positive but insignificant impact on the poverty rate. 3) Job opportunities do not have a direct impact on the poverty rate through unemployment, whereas minimum wage directly affects the poverty rate through unemployment. Keyword : Employment Opportunity, Minimum Wage, Unemployment, Poverty Rate.